Phytotherapeutic drugs with nephroprotective activity (review) - Podpletnyaia E.A.; Khomiak N.V.; Sokolova E.V.; Kaydash S.P.; Khomiak E.V. (Medičnì Perspektivi)
The article analyzes characteristics of chemical composition and pharmacodynamics of phytotherapeutic agents (monopreparations and complexes), used in the treatment of kidney and urinary tract diseases. Analysis of main pharmacological effects of medicinal plants and their complexes was made, comparative characteristics of herbal remedies by indications for use in acute and chronic diseases of the kidneys and urinary tract (pyelonephritis, cystitis, urethritis, glomerulonephritis, nephrolithiasis) and edematous syndrome of various etiologies was carried out. Pharmacological characteristics of diuretic, nephroprotective and nephrolitholytic action of watermelon lyophilized powder according to its composition (flavonoids, macro- and micronutrients, vitamins and so on.) was analyzed. On the basis of data on a wide range of biological activity, sufficient clinical efficacy as adjuvant therapy drugs, as well as good tolerability of herbal remedies, appropriateness and prospects of search for new plant nephroprotective drugs was concluded.